ARTIFICIAL INTELLIGENCE AND THE QUANTUM WORLD: A NEW ERA OF PHYSICS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article discusses the development trends of artificial intelligence and quantum physics, as well as their role in modern science and technology. The fundamental concepts of quantum mechanics, the operating principles of quantum computing systems, and their advantages in data processing are analyzed. In addition, the study examines the new opportunities emerging from the integration of artificial intelligence algorithms with quantum technologies, their efficiency in solving complex computational problems, and promising future directions. The findings indicate that the integration of artificial intelligence and quantum technologies serves as an important factor in the advancement of scientific research and various applied fields.